Efektifitas Prenatal Yoga terhadap Pengurangan Keluhan Fisik pada Ibu Hamil Trimester III - Rafika, Rafika (Jurnal Kesehatan, 2018)
During pregnancy, pregnant women experience physical and psychological changes that can lead to discomfort. One of pregnancy care in the third trimester is yoga exercise. This study was to determine the effectiveness of prenatal yoga in reducing physical discomfort in the third trimester of pregnancy. This was a Quasi-Experimental study with Non-Equivalent Control Group approach. The sample of this study were 32 pregnant women of the third trimester consisting of 16 people as intervention group and 16 people as control taken by consecutive sampling technique. Univariate analysis was performed frequency distribution, Wilcoxon test, and Mann Whitney test. The result showed that the mean difference between pre-test and post-test of the control group was -0.25; (p=0.417>α=0.05). The difference of mean value between pre-test and post-test of the intervention group was 3.5; (p=0,000 <α=0.05). The difference of the mean value of physical discomfort in control and intervention group was 3.75; (p=0.000<α=0,05), it means that there was a significant difference of the mean value of physical discomfort of respondent between control and intervention group. It can be concluded that prenatal yoga has effective to reduce the physical discomfort of a pregnant mother in the third trimester. This study suggests prenatal yoga program could implement in midwifery care especially in the class of pregnant women in Public health center routinely so that the discomfort of pregnant women during pregnancy can be overcome.